ANTI-PLASMODIUM FALCIPARUM IN VITRO ACTIVITY OF CALOPHYLLUM BICOLOR EXTRACT: Morphology and Ultra Structure - Kaseke, Martha Marie; Hadju, Veny; Karim, Syafruddin; Nurdin, Armyn (BALI MEDICAL JOURNAL, 2015)
Background: Anti-malarial resistance of Plasmodium, such as chloroquine becoming a health problem worldwide. This research aims to evaluate the in vitro anti-plasmodium activity of hexane fraction extract of Calophyllum bicolor (C. bicolor) against culture of Plasmodium falciparum (P. falciparum) 3D7 and determine its inhibitor concentration of 50% (IC50); to observe the microscopic changes of P. falciparum after exposed to the hexane fraction of C. bicolor extract and to observe the ultra structure changes of P. falciparum 3D7 after being exposed to hexane fraction of C. bicolor extract. Method: This research applied quasi experimental with post-test only control group design. Anti malarial activity test of hexane fraction of C. bicolor extract towards Plasmodium falciparum 3D7 2% was undertaken over 48 hours with in vitro incubation technique. The level of parasitemia was observed using binocular optical microscope with 1000x magnification by counting the infected erythrocytes with Giemsa color technique. Then it was analyzed to determine the level of inhibitor concentration of 50% (IC50) of the C. bicolor extract. The next step is to observe the changes of parasite’s morphologic and ultra structure after the 24 and 48 hours incubation of the parasite P. falciparum 3D7 with hexane fraction of C. bicolor, IC50. Then, the morphologic change of P. falciparum 3D7 was observed with optical binocular microscopy and the ultra structure changes with Transmission Electron Microscopy (TEM). The changes of morphologic and ultra structure were analyzed qualitatively. Results: The research revealed that hexane fraction of the C. bicolor extract inhibited the growth of the parasite P. falciparum 3D7 with the value of -49.00±2.54, 12.53±3.13, 23.01±1.10, 27.68±4.23, 48.65±18.71, 70.82±4.67, 80.52±6.17% with the hexane extract concentration of 0, 0.001, 0.01, 0.1, 1, 10, 100, and 1000 µg/mL. This research also found that the inhibitor concentration of 50% (IC50) of hexane fraction of C. bicolor extract was 3.94 µg/mL in 10-7 which could change the morphologic and ultra structure of P. falciparum 3D7. There were several changes in morphology of the parasite over 24 hour incubation compared with the control group, i.e. the nucleus of young tropozoid became thicker, darker, and smaller; the skizon were condensate, thicker, darker, karyorrhexis and demolition of membrane. Hexane fraction of C. bicolor extract also changes the ultra structure over 24 hour incubation, i.e. vacuole membrane boundary and hemozoin were unclear. Over 48 hours of incubation the nucleus and cytoplasm bigger than those in the control group. Conclusion: Hexane fraction of the C. bicolor extract showed a strong anti plasmodium activity towards the in vitro culture of P. falciparum 3D7 at the level of (IC50) 3.94 µg/mL. The Hexane fraction of C. bicolor extract could change the morphology and ultra structure of P. falciparum 3D7 in vitro.
Keywords: Calophyllum bicolor; Plasmodium falciparum 3D7, Activity; anti plasmodium